(untitled) (Research, Society and Development, 2022)
Erosion is an area of decreased density, discontinuity, or irregularity of the cortical bone, including the mandibular condyle. This study aimed to assess the location and extent of condyle bone erosion using multislice CT. CT images of 82 TMJ were evaluated from 41 symptomatic patients by two observers. The agreement between both observers was measured through the Kappa coefficient. Bone erosion in the condyle occurred as the following: anterior 1.2% (1 case); superior 62.2% (51 cases); no change 18.3% (15 cases); posterior and superior 12.2% (10 cases); superior and posterior 3.7% (3 cases); superior, anterior, and posterior 2.4% (2 cases). The prevalence of erosion in the condyle occurs predominantly on the upper aspect, with 80.5% of the cases.